Dances with Heads: Parasitic Mimesis and the Government of Savagery in Colonial East Timor - Roque, Ricardo (2018)
This article explores the conjunction between mimesis and parasitism as a colonial mode of relating with forms of ‘savagery’ in state administration in relation to both the colonial Self and indigenous Others. The article examines the participation in 1861 of Portuguese Governor Afonso de Castro in a headhunting ceremony, the ‘feast of the heads’, which was held in colonial East Timor. By following a dispute concerning the problems and merits of the governor’s compliance with this ritual, it conceptualizes the trade with savagery within colonial government praxis as a parasitic form of mimesis. In this context, the dangers of bracketing the self and surrendering to the forces of otherness allowed for headhunting ritual energies to be extracted and exploited to the colonial state’s advantage.